Uji Antagonisme Trichoderma sp. Terhadap Jamur Patogen Alternaria porri Penyebab Penyakit Bercak Ungu Pada Bawang Merah Secara In-Vitro - Muksin, Rusdam; I, Rosmini; Panggeso, Johanis (AGROTEKBIS, 2013)
The objective of this study is to know the ability the fungus Trichoderma sp. as antagonistic to fungal pathogens Alternaria porri (EII. Cif.) on shallot. This study was conducted in the Laboratory of plant pests and Disease Department (HPT), Agriculture faculty of Tadulako University, Palu in Plant Central Sulawesi. This study used the isolation and identification of fungal pathogen A.Porri on onion and antagonism test of Trichoderma sp test against mold growth A.porri, with 2 treatments and 5 replications so that there were 10 experimental units. Local isolates of Trichoderma sp. Used in this experimen were derived from two institusion the Laboratory of plant pests and Diseases Faculty of Agriculture University of Tadulako and BPTP Biromaru. The result of this stady indikate that bolt of lokal isolate Trichoderma sp. quite effective in suppressing the growth fungi A.porri EII. Cif. disease-causing purple spots on the onion crop in-vitro, but percentage of inhibition bolth of isolate ware not significantly different at 5% level test results.